MODEL D&M IS SUCCESS EFEKTIFITAS SIM-LITABMAS DI UPN “VETERAN” JAWA TIMUR - Rosadi, Aswin; Budiyanto, A. Djoko; Sinaga, Benyamin L (Jurnal Sistem Informasi dan Bisnis Cerdas, 2016)
Nowadays, information system has a strategic role in providing support to a university, which provide support for administrative services, as a teaching tool and a means of communication and the use of Information Technology to help make decisions. SIM-LITABMAS application program serves as a replacement nomination process P2M proposals that were previously done manually and will now be done by on-line (on-line proposal). The purpose of this study was to determine the effect of system quality, information quality and service quality to the intention of using, and the net benefit to the lecturers at the Veterans National Development University of East Java. Exogenous variables in this study is the quality of the system, the quality of information and service quality. Intention to use endogenous variables and net benefits. The target population is on the faculty at the University of National Development Veteran East Java. To test the hypothesis used Structural Equation Model. The results of the study are: (1) System quality does not affect the of Intention to Use; (2) Quality of information affect the Intention to Use; (3) The service quality affect the Intention to Use; (4) Intention to Use an effect on net benefits